Chemical Stabilization of Clayey Soil with Polypropylene Fiber Reinforcement for Roadbase Construction - Ahmad Nasri, Abdul Rashid; Chan, Chee-Ming; Rosman, Mohammad Zawawi (Penerbit UTHM, 2020)
Roads are essential as a medium for people to connect and also to improve the economic activities of a country. Khan et al. [1] added that road and highway are the centers of economic activities in all countries where land-based communication is dominant. Due to the population growth, residential and commercial developments are also in high demand. The construction of roads is also increasing to meet the living standard of the population, especially in a rural area. Rural road is mainly used as a pathway to reach plantation and sub-urban areas. However, rural road is at risk due to heavy load agricultural vehicles as it may cause road damages and will affect economic and development activities.